An Ecosystem Approach for The Sustainable Use and Management of the Lake Victoria Ecosystem - Martin Mamboleo (Universitas Diponegoro, 2023)
The key to achieving sustainable development is striking a balance between the exploitation of natural resources for socioeconomic development and the preservation of ecosystem services, which are essential to everyone's well-being and livelihood. This can be achieved by using the ecosystem approach which promotes fair conservation and sustainable use of both land, water and living resources. Over the years, human activities have played an important role in the degradation of natural ecosystems, either due to pollution or unsustainable development. Lake Victoria is the best example of the impact of anthropogenic activity on ecosystems, as it has undergone dramatic biophysical and geochemical changes in a relatively short time. Managing Lake Victoria requires the coordinated efforts of individuals, landowners, research institutions, community groups, and the government. This lake is an important group of natural resources due to its ecosystem services and often unique cultural characteristics hence need for sustainable management. This article focuses on using the ecosystem method to determine optimal management approaches for the Lake Victoria ecosystem's long-term sustainability. The article proposes an integrated stakeholder-based management system and holistic regional development in lake areas that will preserve natural ecosystems without compromising the sustainable use of ecosystem services. As a result, there is a need to remedy the lake ecosystem's degradation in order to retain the shared ecological services that support socioeconomic well-being.